Cyclin E facilitates dysplastic hepatocytes to bypass G1/S checkpoint in hepatocarcinogenesis. Issue 9 (22nd August 2013) - Pok, Sharon; Wen, Victoria; Shackel, Nicholas; Alsop, Amber; Pyakurel, Pawan; Fahrer, Aude; Farrell, Geoffrey C; Teoh, Narci C
Abstract: Background and Aim: By array‐comparative genomic hybridization, we demonstrated cyclin E as one of seven genes associated with hepatocellular carcinoma (HCC) development in Ku70 DNA repair‐deficient mice. We therefore explored the hypothesis that during hepatocarcinogenesis, cyclin E kinase can overcome the inhibitory effects of p53 and establish whether abnormal miRNA(mi‐R)‐34, a co‐regulator of cyclin E and p53, can account for their interactions as "drivers" of HCC. Methods: Dysplastic hepatocytes (DNs) and HCCs were generated from diethylnitrosamine (DEN)‐injected C57BL/6 male mice at 3–12 months. Results: Cyclin E/cdk2 was barely expressed in normal liver, but was readily detected in dysplastic hepatocytes, localizing to glutathione‐S transferase pi‐form positive cells dissected by laser‐dissection. Cyclin E kinase activity preceded cyclin D1, proliferating cell nuclear antigen expression in DNs and HCCs despite maximal p53 and p21 expression. We confirmed that cyclin E, rather than cyclin D1, is the proliferative driver in hepatocarcinogenesis by immunoprecipitation experiments demonstrating preferential binding of p21 to cyclin D1, allowing cyclin E‐mediated "escape" from G1/S checkpoint. We then showed cyclin E was responsible for regulating wild‐type p53 by knockdown experiments in primary HCC cells; cyclin E‐knockdown increased p53 and p21, diminished anti‐apoptotic Bcl‐XL and reduced cell viability. Conversely, blocking p53 augmented cyclin E, Bcl‐XL expression and increased proliferation. Physiological interactions between cyclin E/p53/p21 were confirmed in primary hepatocytes. miR‐34a, c were upregulated in dysplastic murine, human liver and HCCs compared with normal liver, and appeared to be linked to cyclin E/p53. Conclusion: Upregulation of functionally active cyclin E via miR34 with loss of p53 function is associated with cell‐cycle checkpoint failure increasing proliferative drive that favors hepatocarcinogenesis.